2020
DOI: 10.15252/emmm.201911902
|View full text |Cite
|
Sign up to set email alerts
|

An IgG‐based bispecific antibody for improved dual targeting in PSMA‐positive cancer

Abstract: The prostate‐specific membrane antigen (PSMA) has been demonstrated in numerous studies to be expressed specifically on prostate carcinoma cells and on the neovasculature of several other cancer entities. However, the simultaneous expression of PSMA on both, tumor cells as well as tumor vessels remains unclear, even if such “dual” expression would constitute an important asset to facilitate sufficient influx of effector cells to a given tumor site. We report here on the generation of a PSMA antibody, termed 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…Upregulation of CD11a/CD18 occurs in response to cytokines and chemokines [27] commonly produced upon CD3-induced off-target T cells activation [22,23,25,28,29]. We have shown that a high binding affinity to CD3 apparently favors this effect [11]. Initial efforts to generate CD3-containing bsAb antibodies were often biased towards using highaffinity CD3 binders, which triggered not only potent tumor cell killing, but also high levels of cytokine release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upregulation of CD11a/CD18 occurs in response to cytokines and chemokines [27] commonly produced upon CD3-induced off-target T cells activation [22,23,25,28,29]. We have shown that a high binding affinity to CD3 apparently favors this effect [11]. Initial efforts to generate CD3-containing bsAb antibodies were often biased towards using highaffinity CD3 binders, which triggered not only potent tumor cell killing, but also high levels of cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether the off-target T cell activation correlates with the CD3 binding affinity, we compared the activity of the Fabsc antibody with that of an IgGsc molecule comprising the same CD3 single chain. However due to spatial restrictions the affinity of the CD3 moiety in the IgGsc molecule is considerably lower and in contrast to the Fabsc molecule [11], this antibody showed no off-target T cell activation (Figure S1). The latter also holds true for a Fabsc molecule containing a low-affinity single-chain CD3 binder, indicating that regardless of CD3 binding valency and the bsAb format, only high CD3 binding affinity can contribute to true off-target activation.…”
Section: Off-target T Cell Activation Upon Bsab Binding In the Absence Of Target Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Present strategies comprise checkpoint inhibition, Ref. [ 41 ] transfection with chimeric antigen receptors (CARs) [ 42 ] or application of bispecific antibodies to mobilize T cells, components of the adaptive immune system [ 43 , 44 ], against cancer. Stimulation of NK cells as cytotoxic lymphocytes of the innate immune system constitute an alternative to the promise, which is exemplified by their contribution to the efficacy of Her2/neu antibody Trastuzumab, where they mediate potent antibody-dependent cellular cytotoxicity (ADCC) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, further data are needed to fully elucidate the bioavailability of our NKG2D BFP in the sarcoma TME in a clinical setting. For bispecific antibodies it is known that a PSMAxCD3 antibody applicated in vivo penetrates tumor tissue, specifically localizes at the tumor site and attracts immune effector cells (46).…”
Section: Discussionmentioning
confidence: 99%